Inclusion of preschool children into organized activity in leisure time - Milenko Janković; Karolina Berenji; Zoran Milić; Sandra Vujkov (Exercise and Quality of Life)
All physical activity of preschool children during the day occurs while they are in kindergarten or during their leisure time. The aim of the study was to present the results related to the participation of children in organized activities during leisure time and what is the perception of parents about the scope of their children's physical activity and the time spent on watching TV, using computers and playing video games (as a part of wider study). The research was conducted in 2017 in the Preschool institution “Naša Radost” in Subotica. The survey questionnaire was filled in by 135 parents for children of the average age of 5.14 years (±0.91). The survey questionnaire contained questions about children's nutrition (NutriStep survey) and their involvement in organized activities with educational and sports-recreational content during leisure time, as well as parent’s opinion on quantity in child’s sedentary activities. 65.9% of children aged 5 to 7 was found to attend some kind of organized activity, most often within programs of foreign language schools, sports schools and programs with aesthetic  presentation of skills is important (ballet, dance and folklore). The largest number of parents reported that their child spent one hour watching TV, using a computer or playing games. About 71% of parents reported that their child was physically active enough. In both cases, a statistically significant difference was found between boys and girls. Within the family circle and within the educational institution, where children spend most of the time, it is necessary to provide conditions for undisturbed growth and development. One of the best ways is through exercising physical activity.